Implementation of a Multifaceted Interactive Electrodiagnostic Medicine Workshop in a Physical Medicine and Rehabilitation Residency Program. (February 2018) - Donovan, Jayne; van de Rijn, Marc; McCabe, Elizabeth L.; Shih, Shirley; Paganoni, Sabrina
Abstract : Abstract: Electrodiagnostic medicine is a required component of Physical Medicine and Rehabilitation residency education, but limited resources exist to guide curriculum development. Our objective was to create a focused workshop to enhance our residency program's electrodiagnostic curriculum. We created two separate 1.5-day workshops, one basic and one advanced, for all residents. Each workshop included didactic sessions, case discussion, question and answer sessions, demonstrations, and hands-on participation with direct supervision and feedback. Presurveys and postsurveys were administered to evaluate the value of the workshops. We also assessed trends in electrodiagnostic self-assessment examination scores. Residents reported clinical electrodiagnostic rotations to be more valuable to their education than previous didactic sessions and independent learning. Self-reported knowledge of electrodiagnostic concepts, resident comfort level in planning, performing, and interpreting studies, and perceived value in independent learning of electrodiagnostic medicine improved after implementation of the workshops. There was a 7% improvement in the American Association of Neuromuscular and Electrodiagnostic Medicine electrodiagnostic self-assessment examination score compared with the previous year and a 15% improvement in the Physical Medicine and Rehabilitation self-assessment examination electrodiagnostic subscore compared with the previous 5 yrs. All participants recommended similar educational experience for other residents. This successful workshop may serve as a resource for other training programs. Abstract : Supplemental digital content is available in the text.